Do post à conexão: o papel das relações públicas na gestão de comunidades de nicho no Instagram - Berton, Giulia Mussatto (My University, 2025)
This study aims to analyze the role of Public Relations in the construction, management, and strengthening of engagement within niche communities, with an emphasis on the social network Instagram. The investigation was motivated by the noticeable growth of these thematic communities on social media, both in number and in strategic relevance for brands, as well as by the existence of a considerable gap in academic literature on the subject. The research, qualitative, applied, and exploratory in nature, was developed through bibliographic research for the construction of the theoretical framework, virtual ethnography with non-participant observation for data collection, and content analysis according to Bardin's (2011) methodology for the interpretation of results. The theoretical framework presents essential topics for understanding digital communication processes, including the characteristics of digital communication (Saad Corrêa, 2005); the concept of the "user-as-media" (Terra, 2011); creator economy and UGC; Dreyer's (2015; 2021) Public Relations methodologies; typologies and foundational principles of digital communities (Bradley & McDonald, 2012; Recuero, 2006; Armstrong & Hagel III, 1996); the role of the community manager; and the limitations of Public Relations in the management of digital communities. The empirical corpus selected for virtual ethnography and subsequent content analysis consisted of the communities Obvious and Respirar e Agradecer, whose published content was observed and cataloged between September 1 and 30, 2025. The results indicate that, although the communities share similar structures, they adopt distinct communicational approaches. The study also revealed the presence of essential Public Relations competencies, such as strategic vision, audience research, and image management, integrated into the dynamics of digital communication. It is concluded that Public Relations strategies are crucial for the management and sustainability of niche communities, serving as pillars for building meaningful relationships between brands and their audiences, and contributing to the growth, consolidation, and longevity of these communities within the Instagram environment. [resumo fornecido pelo autor]
Este trabalho tem como objetivo a análise do papel das Relações Públicas na construção, gestão e fortalecimento do engajamento em comunidades de nicho, com ênfase na rede social Instagram. A investigação partiu da constatação do crescimento expressivo dessas comunidades temáticas nas redes sociais, tanto em número quanto em relevância estratégica para as marcas, bem como da existência de uma lacuna de literatura acadêmica sobre o tema. A pesquisa, de natureza qualitativa, aplicada e exploratória, foi desenvolvida por meio de pesquisa bibliográfica para construção do referencial teórico, etnografia virtual com observação não participativa para coleta de dados e análise de conteúdo segundo Bardin (2011) para interpretação dos resultados. O referencial teórico traz conceitos essenciais para a compreensão das dinâmicas comunicacionais na era digital, citando as características da comunicação digital (Saad Corrêa, 2005), a figura do usuário-mídia (Terra, 2011), conceitos como creator economy e UGC, as metodologias de Relações Públicas de Dreyer (2015; 2021), as tipologias e fundamentos das comunidades digitais (Bradley e McDonald, 2012; Recuero, 2006; Armstrong e Hagel III, 1996), o conceito de gestor de comunidades e as limitações das Relações Públicas na gestão de comunidades. O corpus empírico selecionado para etnografia virtual e, posteriormente, análise de conteúdo, foi composto pelas comunidades Obvious e Respirar e Agradecer, cujos conteúdos publicados foram observados e catalogados entre 01 e 30 de setembro de 2025. Os resultados apontam que, embora as comunidades apresentam estruturas semelhantes, adotam abordagens comunicacionais distintas. O estudo evidenciou, ainda, a presença de competências fundamentais das Relações Públicas, como visão estratégica, pesquisa de públicos e gestão de imagem, aplicadas de forma integrada à dinâmica digital. Conclui-se que as estratégias de Relações Públicas são determinantes para a gestão e sustentabilidade de comunidades de nicho, atuando como pilares na construção de relacionamentos significativos entre marcas e públicos, e contribuindo para o crescimento, a consolidação e a perenidade das comunidades no ambiente do Instagram. [resumo fornecido pelo autor]
Keywords: comunicação digital; relações públicas; comunidades de nicho; Instagram; digital communication; public relations; niche communities; Instagram